Four-mode parallel silicon multimode waveguide crossing scheme based on the asymmetric directional couplers - Zhang, Runsen; Sun, Shangsen; Zhang, Fengchun; Chen, Kaixuan; Liu, Liu; Zhu, Ning (Optics express, 2022)
We theoretically propose and experimentally demonstrate a novel ultra-compact four-mode silicon waveguide crossing device based on the asymmetric directional couplers for densely integrated on-chip mode division multiplexing systems. The crossing is based on the parallel crossing scheme where the two access waveguides are parallel to each other to have minimal area. The device utilizes an idle high order mode inside one bus waveguide to drop subsequently all the guided modes inside another bus waveguide, with the help of the asymmetric directional couplers (ADCs). We also optimize the structural parameters of these ADCs by using the particle swarm optimization method to obtain higher conversion efficiency and smaller coupling length. The simulation results show that the insertion losses of the input 1-8 ports are no more than 0.5 dB at the central wavelength of 1550 nm. And the crosstalks are less than −20 dB in the broadband from 1530 nm to 1580 nm with a footprint of only 25 × 70 µm 2 . Furthermore, our scheme can be easily extended to accommodate more modes by cascading more ADCs for mode dropping and crossing, without obviously deteriorating the performance and greatly increasing the overall footprint.